Consistent Large‐Scale Response of Hourly Extreme Precipitation to Temperature Variation Over Land. Issue 4 (21st February 2021) - Ali, Haider; Fowler, Hayley J.; Lenderink, Geert; Lewis, Elizabeth; Pritchard, David
Abstract: Hourly precipitation extremes can intensify with temperature at higher rates than expected from thermodynamic increases explained by the Clausius‐Clapeyron (CC) relationship (∼6.5%/K), but local scaling with surface air temperature is highly variable. Here we use daily dew point temperature, a direct proxy of absolute humidity, to estimate at‐gauge local scaling across six macro‐regions for a global data set of over 7, 000 hourly precipitation gauges. We find scaling rates from CC to 2 × CC at more than 60% of gauges, peaking in the tropics at a median rate of ∼1.5CC. Moreover, regional scaling rates show surprisingly universal behavior at around CC, with higher scaling in Europe. Importantly for impacts, hourly scaling is persistently higher than scaling for daily extreme precipitation. Our results indicate greater consistency in global scaling than previous work, usually at or above CC, with positive scaling in the (sub)tropics. This demonstrates the relevance of DPT scaling to understanding future changes. Plain Language Summary: Globally, hourly precipitation extremes have increased during recent decades and are projected to intensify more in the future. Therefore, understanding the relationship of precipitation extremes with temperature may be helpful for risk assessment and in decision making for climate adaptions. Using station‐based observations of hourly precipitation and daily dewpoint temperature, we show that precipitation extremes increase with the increase in dewpoint temperature consistently at a regional scale, and even with a higher rate at the gauge‐level. This rate of increment is much higher than that for daily extreme precipitation. Our results have implications for understanding drivers of changes to extreme precipitation at different spatial scales. Key Points: Hourly extreme precipitation consistently follows at least the CC rate at a regional scale, and often a super‐CC rate at the gauge‐level The median scaling is greater than CC rate for gauges in wet and dry regions Regional scaling curves consistently follow the CC rate in the temperate climate zone